Charge selective contacts, mobile ions and anomalous hysteresis in organic–inorganic perovskite solar cells1. Issue 3 (27th May 2015) - Zhang, Ye; Liu, Mingzhen; Eperon, Giles E.; Leijtens, Tomas C.; McMeekin, David; Saliba, Michael; Zhang, Wei; de Bastiani, Michele; Petrozza, Annamaria; Herz, Laura M.; Johnston, Michael B.; Lin, Hong; et al.
<x xml:space="preserve">Abstract</x> "Compact layer-free" perovskite devices yield negligible stabilised power output, in comparison to those with charge selective contacts, elucidating mechanism for hysteresis.